Youth suicide in Buryatia? - S. V. Tsyrempilov (Acta Biomedica Scientifica, 2013)
The article presents the data on the high level of suicides in Buryatia. Unfavorable situation is observed in areas with prevalence of indigenous population. In Kizhinginskiy, Eravninskiy, Khorinskiy, Okinskiy, Severobaikalskiy areas number suicides in recentyears was more than 100 cases per 100 thousand population. The largest number of suicide was registered at the age of 16-25 years: in 2007 the percent of these suicides was 30,1 % of the total number of suicides. The influence of socio-economic and health conditions of organizational factors on population suicide rate is unfavorable. It was suggested that level of suicides depends on the belonging to different ethnic groups. There are huge differences between regions of Russia by the number of suicides. It was suggested that ethnic behavior, including so-called suicidal behavior, of the representatives of different ethnic groups is determined by the stage of ethnogenesis. The individuals with an increased risk of suicide among young people of different nationalities were determined. Also we revealed large number of people with an increased risk of suicide. It was determined that belonging to different ethnic groups had no significant effect on the number of persons with increased risk of suicide.